SYSTEMATIC LITERATURE REVIEW (SLR): KOMPETENSI KERJA KRU DALAM MENINGKATKAN KEPUASAN PENGGUNA LAYANAN SUROBOYO BUS - Noeraini, Lailatul; Atho’iillah, Akhmad Yunan (Relawan Jurnal Indonesia, 2025)
This study aims to systematically analyze the relationship between crew competence and work discipline with the level of user satisfaction of public transportation services, specifically on the Suroboyo Bus in Surabaya City. The research method used is a Systematic Literature Review (SLR) by collecting and evaluating relevant scientific articles from various sources, such as Google Scholar, Scopus, and ScienceDirect. The results of the study indicate that crew competence, which includes technical skills, service knowledge, and communication skills, has a significant influence in creating a positive service experience. Work discipline, such as punctuality, adherence to standard operating procedures (SOP), and professionalism, is also an important factor in building user trust and satisfaction. This study provides practical implications for public transportation management in designing more effective crew training and supervision strategies. In addition, the results of this study can also serve as a reference for local governments and public transportation managers in improving service quality to support sustainable transportation development in urban areas.